دور التسويق الالكتروني في تنمية المشاريع لدى الحرفيات بولاية الاغواط - بن جديعة فايزة; جميخ فاطمة الزهراء; د/ تواتي خضرون (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة باللغة العربية سعت هذه الدراسة لتحقيق العديد من الأهداف، وخاصة توضيح وضبط مفهوم التسويق الالكتروني، ومختلف مصادره، وكذلك معرفة كيف يمكن للتسويق الإلكتروني مساعدة الحرفيات في تعزيز علامتهن التجارية، كما هدفت هذه الدراسة إلى معرفة الأساليب التي تتبعها الحرفيات في تسويق منتجاتهم الحرفية، ومحاولة الخروج ببعض الاقتراحات التي يمكن أن تستفيد منها حرفيات مدينة الأغواط بشكل خاص. وتندرجدراستناضمنالدراساتالوصفيةالتحليلية (المنهجالوصفيالتحليلي) للتسويقالالكترونيلدىالحرفياتالذيتتمحورالدراسةحولهذلكبتحليلهاتحليلامنهجيادقيقابغيةالوصولإلىالمعاينالخفيةوالباطنيةالتيتحملهاعينةالدراسةوذلكباعتمادعلىالمنهجالمناسب، وتمالإعتمادفيدراستناعلىالعينةالعشوائيةالطبقيةبحيثتمثلمجتمعبحثنافي 40 حرفيةعلىمستوىمدينةالأغواط. تمثلتأداةدراستنافيالإستبيان،فهويعتبرواحدةمنأهمالأدواتالتييستخدمهاالباحثونعنددراستهملظاهرةمعيّنةأولجمعمعلوماتتساعدهمفيالحصولعلىنتائجهامّةفيأبحاثهم. وقد تم التوصل في دراستنا إلى مجموعة من النتائج أن : • يمكنأنيساهمالتسويقالإلكترونيفيمساعدةالحرفياتلتطويرمشاريعهمالحرفية. • يمكنللتسويقالإلكترونيمساعدةالحرفياتفيتعزيزعلامتهنالتجاريةومنتجاتهنلدىالجمهور. • يمكنللتسويقالإلكترونيأنيساعدالحرفياتفيتحديدوإستهدافالجمهورمنخلالمواقعالتواصلالإجتماعي. • هناكأساليبتتبعهاالحرفياتفيتسويقمنتجاتهنالحرفية، نذكر منها : تطبيق تيك توك، إنستغرام، عبر صفحات الفيس بوك...إلخ. الكلمات المفتاحية: دور، التسويق الإلكتروني، تنمية المشاريع، الحرفيات. Summary of the study in English This study sought to achieve many objectives, especially clarifying and controlling the concept of e-marketing, and its various sources, as well as knowing how e-marketing can help craftswomen in strengthening their brand, and this study also aimed to know the methods followed by craftswomen in marketing their craft products, and try to come up with some suggestions that can benefit the craftswomen of the city of Laghouat in particular. Our study falls within the descriptive analytical studies (descriptive analytical approach) for e-marketing among craftswomen, which the study revolves around by analyzing it systematically in order to reach the hidden and esoteric previews carried by the study sample, depending on the appropriate approach, and our study was based on the stratified random sample so that it represents our research community in 40 craftswomen at the level of the city of Laghouat. The tool of our study was the questionnaire, which is considered one of the most important tools that researchers use when studying a particular phenomenon or to collect information that helps them obtain important results in their research. In our study, a set of results were reached that: • E-marketing can help craftswomen develop their craft projects. • E-marketing can help craftswomen promote their brand and products to the public. • E-marketing can help craftswomen identify and target audiences through social networking sites. • There are methods followed by craftswomen in marketing their craft products, including: TikTok, Instagram, through Facebook pages... Etcetera. Keywords: role, e-marketing, enterprisedevelopment, craftswomen